Substantially Increased Plasma Coproporphyrin‐I Concentrations Associated With OATP1B1*15 Allele in Japanese General Population - Yosuke Suzuki; Yuri Sasamoto; Teruhide Koyama; Chisato Yoshijima; Masahiro Nakatochi; Michiaki Kubo; Yukihide Momozawa; Ritei Uehara; Keiko Ohno (Wiley, 2021)
Coproporphyrin‐I (CP‐I) in plasma is a sensitive and specific endogenous probe for phenotyping organic anion transporting polypeptides 1B (OATP1B, encoded by SLCO1B). A few small‐scale studies suggested that plasma CP‐I concentration is affected by OATP1B1 polymorphism, but detailed studies are lacking. In this large‐scale study, we measured plasma CP‐I concentrations in 391 subjects from the Japanese general population, and evaluated the relationship between plasma CP‐I concentrations and OATP1B1 polymorphisms to further assess the utility of plasma CP‐I concentrations as an endogenous OATP1B probe. Plasma CP‐I concentrations were 0.45 ± 0.12, 0.47 ± 0.16, 0.47 ± 0.20, 0.50 ± 0.15, 0.54 ± 0.14, and 0.74 ± 0.31 ng/mL in participants with OATP1B1*1b/*1b (n = 103), *1a/*1b (n = 122), *1a/*1a (n = 40), *1b/*15 (n = 74), *1a/*15 (n = 41), and *15/*15 (n = 11), respectively, showing an ascending rank order with significant difference (P < 0.0001). Post hoc analysis revealed significant increases in plasma CP‐I concentration in OATP1B1*1b/*15 (P = 0.036), *1a/*15 (P = 0.0005), and *15/*15 (P = 0.0003) groups compared with the OATP1B1*1b/*1b group. There was no significant difference among OATP1B genotypes in plasma concentration of 3‐carboxy‐4‐methyl‐5‐propyl‐2‐furanpropanoic acid, a uremic toxin reported to decrease OATP1B activity in vivo. These findings confirm the utility of plasma CP‐I concentrations as an endogenous biomarker for phenotyping of OATP1B activity. Plasma CP‐I concentration is potentially useful for the study of drug‐drug interactions via OATP1B or individual dose adjustment of OATP1B substrates.